Mindsets and Strategies for Negotiation Success. - Negotiation Institute, American; Christian, Kwame (linkedin.com, 2021)
In this course, adapted from the Negotiate Anything podcast, Lousin Mehrabi discusses the mindset and strategies that you need for a successful negotiation.